Let the cameras roll and the paints flow : a thesis on the photographic tableau - Yang, Leonard (2015)
Just as the Calotype and the Daguerreotype were invented by Fox Talbot and Louis Daugerre respectively in the 1830s, with the former labeled as a ‘pencil of nature’ by its inventor, today’s camera is a device that captures reality and discloses a slice of reality that appears somewhat more spectacular than the circumstances we are in due to the proliferation of intermediary platforms capable of presenting a plethora of images that augment reality to the standard of the photogenic. The assumed authenticity of the photograph is in a state of crisis – its capacity to serve as realistic representation is warped beyond means of redemption. But what is reality other than a subjective perspective? What is reality other than staring into the stillest waters and having the reflection of our own face staring back at us, with the occasional ripple wiping clean a wrinkle that represents the loss of youth and the coming of age?